Generación sobre la base Sig del mapa geomorfológico, escala 1: 25.000, orientado a la gestión territorial del cantón Olmedo, provincia de Loja. - Pasaca Lafebre, Dennis Alexander (2018)
The application of GIS technologies has become an important tool to handle and the digital terrain analysis (DTA) for cartographical aims.From this point of view, the present project has included as research topic; the elaboration of database with the purpose of storing digital information; the quantitative characteristic of the landscape throughout automatic classification techniques based on DEM and the 3D digital interpretation, with the data from remote detection. These items, detail the content of the technical memory that manage the development of the pattern of morphological units in Olmedo town at a scale of 1: 25.000, as a support to its physical management of its territory. Together the legend was built in reference to the cartographical geomorphological mapping system of the Ecuadorian Space Institute. The final results determined a total of 185 geological shapes, associated to 8 morphological units, from 4 genetic classes.